1997
DOI: 10.1021/bi962074m
|View full text |Cite
|
Sign up to set email alerts
|

[125I]Iberiotoxin-D19Y/Y36F, the First Selective, High Specific Activity Radioligand for High-Conductance Calcium-Activated Potassium Channels

Abstract: Iberiotoxin (IbTX), a selective peptidyl ligand for high-conductance Ca2(+)-activated K+ (maxi-K) channels cannot be radioiodinated in biologically active form due to the importance of Y36 in interacting with the channel pore. Therefore, an IbTX double mutant (IbTX-D19Y/Y36F) was engineered, expressed in Escherichia coli, purified to homogeneity, and radiolabeled to high specific activity with 125I. IbTX-D19Y/Y36F and [127I]IbTX-D19Y/Y36F block maxi-K channels expressed in Xenopus laevis oocytes with equal pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 45 publications
8
54
0
Order By: Relevance
“…The difficulties obtaining suitable SK channel antibodies with high selectivity were mostly attributable to the very low expression density of SK channel protein in mammalian brain (based on radioligand binding data using the SK channel ligand [ 125 I]apamin). This toxin labels only 20 -40 fmol of binding sites/mg of protein, a density 10 times lower than for BKchannels (as measured by [ 125 I]iberiotoxin binding; Koschak et al, 1997) or only 1% of the density of toxin-sensitive voltagegated K ϩ channels (e.g., measured by [ 125 I]hongotoxin binding; Koschak et al, 1998) in the same membrane preparation.…”
Section: Discussionmentioning
confidence: 97%
“…The difficulties obtaining suitable SK channel antibodies with high selectivity were mostly attributable to the very low expression density of SK channel protein in mammalian brain (based on radioligand binding data using the SK channel ligand [ 125 I]apamin). This toxin labels only 20 -40 fmol of binding sites/mg of protein, a density 10 times lower than for BKchannels (as measured by [ 125 I]iberiotoxin binding; Koschak et al, 1997) or only 1% of the density of toxin-sensitive voltagegated K ϩ channels (e.g., measured by [ 125 I]hongotoxin binding; Koschak et al, 1998) in the same membrane preparation.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that measured equilibrium constants for block and binding of charybdotoxin and IbTx are strongly dependent upon the ionic strength of the extracellular assay medium (Anderson et al, 1988;Garcia-Calvo et al, 1991;Vasquez et al, 1989;Koschak et al, 1997) and the association of particular isoforms of four known accessory beta subunits with the BK channel alpha subunit in native tissues (Hanner et al, 1997;Wallner et al, 1999;Giangiacomo et al, 2000;Meera et al, 2000). For example when the BK channel is coexpressed with the β1 subunit, the dissociation rate of ChTx is slowed by ∼10-fold (Hanner et al, 1997;Gianciacomo et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Materials-An iberiotoxin double mutant was engineered, purified, and radioiodinated with 125 I ( 125 I-IbTX-D19Y/Y36F) as described previously (29). Isradipine ((ϩ)-3 H-PN200 -110) was obtained from PerkinElmer Life Sciences.…”
Section: Methodsmentioning
confidence: 99%
“…1A, rat brain membranes were labeled with the modified BK-specific scorpion toxin IbTX ( 125 I-IbTX-D19Y/Y36F). In earlier studies this double mutated radiolabeled toxin has been demonstrated to interact specifically with BK channels in a manner no different from native IbTX (29,33). Labeled membranes were subsequently precipitated with antibodies raised against different kinds of voltage-gated Ca 2ϩ channels.…”
Section: Optimization Of Immunoprecipitation Studies-functionalmentioning
confidence: 99%